Characterization of antibodies to smooth muscle myosin kinase and their use in localizing myosin kinase in nonmuscle cells. - de Lanerolle, P (1981)
Antibodies to myosin light chain kinase, purified from turkey gizzard smooth muscle, were developed in rabbits and purified by affinity chromatography on a myosin light chain kinase-Sepharose 4B column. The purified antibodies crossreact with purified smooth muscle myosin light chain kinase but not with a variety of contractile or cytoskeletal proteins. The antibodies inhibit the catalytic activity of smooth muscle myosin light chain kinase and there is an inverse relationship between the kinase activity and the amount of antibody present in an assay. Half-maximal inhibition of myosin kinase activity occurs at an antibody/myosin kinase molar ratio of 10:1. The affinity-purified antibodies to smooth muscle myosin kinase were used to study the location of myosin kinase in a variety of nonmuscle cells. Immunofluorescence studies indicate that myosin light chain kinase is localized on microfilament bundles (stress fibers) in cultured fibroblasts. The stress fiber staining pattern is abolished when the antibodies are incubated with purified smooth muscle myosin light chain kinase prior to staining cells, while the staining pattern is unaffected when the antibodies are incubated with actin, myosin, alpha-actinin, or tropomyosin prior to staining. Moreover, the stress fiber staining pattern is periodic in well-spread gerbil fibroma cells and experiments have demonstrated that myosin light chain kinase appears to have the same periodic distribution as myosin but an antiperiodic distribution relative to alpha-actinin. These data indicate that myosin light chain kinase and its substrate, myosin, are in close proximity and are consistent with the hypothesis that myosin light chain kinase regulates actin-myosin interactions in nonmuscle cells.